The Influence of Barcode Scanning Payment System on Customer Satisfaction in Buying and Selling Transactions in Indonesia and India - Achbar Adi Saputra; Dwi Nita Aryani; Ritika Gahlaut; Lim Sheue Hui; Reetika Aggarwal; Nahian Sattar; Mohammed Shiyas (AIBPM Publisher, 2024)
In this era of digitalization, everything has changed, especially in the payment system. The payment system most often used in businesses involves barcode scanning, and this trend is skyrocketing. This research aims to test and analyze the effect of barcode scanning payment systems on customer satisfaction in Indonesia and India, focusing on systems such as QRIS in Indonesia and BharatQR and UPI QR in India. This study is quantitative research. Data was collected by distributing questionnaires to 50 respondents in India and 57 respondents in Indonesia, totaling 107 respondents. The independent variables are ease of use, trust, efficiency, usefulness, and safety, while customer satisfaction is the dependent variable. The data was analyzed using SPSS. The results exhibit that efficiency and security significantly impact customer satisfaction, while ease of use, trust, and usefulness do not affect customer satisfaction. These findings enrich the theory of customer satisfaction and provide valuable suggestions for financial regulators.